The mechanism of cryptocurrency adoption as a means of payment in business - J. V. Mickiewicz (Путеводитель предпринимателя, 2024)
This article examines the theoretical foundations and conceptual specifics of the mechanism for adopting cryptocurrencies as a payment method in business. It discusses the definition and key features of this mechanism, along with summarizing essential recommendations for the use of cryptocurrencies and crypto assets in business payments. The cryptocurrency adoption framework is analyzed through the organizational–economic mechanism, aiming to achieve practical objectives such as cost reduction, improved access to cross–border payments, and transaction security with crypto assets. The article stresses the importance of risk analysis related to cryptocurrency use and the development of risk mitigation methods through proactive management and the application of appropriate tools. The conclusions highlight the feasibility and benefits of using an organizational–economic mechanism to incorporate crypto assets into business payment processes, ensuring efficiency and adaptability of crypto assets or other alternative payment instruments. The study’s novelty lies in its contribution to the development of a mechanism for integrating cryptocurrencies into business operations, while its theoretical value is in the synthesis and clarification of key issues related to cryptocurrency acceptance in business. The proposed concept and vision of the organizational–economic mechanism to enhance the efficiency of cryptocurrency use in business payments offer valuable insights for future research and practical implementation.